Transforming Employee Performance : The Role of Motivation, Leadership, and Culture (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
This study aims to examine the effect of work motivation, leadership, and organizational culture on employee performance at the Pracimantoro Community Health Center, Wonogiri Regency. The research adopts a quantitative approach, utilizing primary data collected through questionnaires distributed to all 37 employees of the health center, who simultaneously serve as the sample of the study. The variables analyzed include work motivation, leadership, organizational culture, and their relationship with employee performance, measured through multiple linear regression analysis using SPSS for Windows. The results indicate that work motivation has a significant and positive effect on employee performance, suggesting that employees with higher levels of motivation are more likely to achieve better work outcomes. Conversely, leadership and organizational culture do not exhibit a statistically significant influence on performance, implying that in this specific organizational setting, these factors may play a lesser role or be mediated by other variables. These findings highlight the importance of implementing targeted strategies to boost work motivation, such as providing fair incentives, fostering opportunities for career advancement, and creating a supportive and engaging work environment. By enhancing motivation, organizations can potentially improve the quality of services delivered to the community. Additionally, the study underscores the need for continuous employee development programs to maintain high levels of performance in public health institutions. Future research is recommended to expand the population scope, include comparative analyses across different community health centers, and explore additional variables such as job satisfaction, workload, or employee engagement. This would enrich the understanding of performance determinants and offer more comprehensive insights for policy formulation in the healthcare sector.